The finite element method - Zienkiewicz, O. C.; Taylor, Richard Lawrence; Nithiarasu, Perumal; Zhu, J. Z. (Oxford ; New York : Elsevier/Butterworth-Heinemann, 2005)
The sixth editions of these seminal books deliver the most up to date and comprehensive reference yet on the finite element method for all engineers and mathematicians. Renowned for their scope, range and authority, the new editions have been significantly developed in terms of both contents and scope. Each book is now complete in its own right and provides self-contained reference; used together they provide a formidable resource covering the theory and the application of the universally used FEM. Written by the leading professors in their fields, the three books cover the basis of the method, its application to solid mechanics and to fluid dynamics. * This is THE classic finite element method set, by two the subject's leading authors * FEM is a constantly developing subject, and any professional or student of engineering involved in understanding the computational modelling of physical systems will inevitably use the techniques in these books * Fully up-to-date; ideal for teaching and reference.
Vol. 1--The finite element method: its basis and fundamentals ; vol. 2--The finite element method: for solid and structural mechanics ; vol. 3--The finite element method for fluid dynamics.
Previous ed.: 2000.
Includes bibliographical references and indexes.
Keywords: Finite element method; Finite element method -- Data processing; Finite element method -- Computer programs; Fluid dynamics; Electronic books